2017
DOI: 10.1364/oe.25.030764
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-crystal tunable color filters based on aluminum metasurfaces

Abstract: Designing color pixels using plasmonic nanostructures and metasurfaces has become a luring area of research in recent years. Here, we experimentally demonstrated the voltage tunability of a dynamic plasmonic color filter by using an aluminum grating integrated with the nematic liquid crystal (LC). Along with a typical substrate coated with rubbed polyimide film, the aluminum grating itself serves as a molecular alignment layer to form a twisted LC cell. This hybrid structure allows electrically controlled tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…Although our work focuses on the theoretical design of the tunable valley state excitations, it can also be achieved practically. As many previous works about the realization of tunable nano-devices based on the electro-optics effect of LCs [41,42], our proposed structures are also able to be fabricated with the help of modern nano- machining technologies. In addition, the special requirement for the excitation of valley states can be easily solved by using point-like chiral sources composed of four-antenna with proper phase lags and narrow Gaussian beams.…”
Section: Discussionmentioning
confidence: 91%
“…Although our work focuses on the theoretical design of the tunable valley state excitations, it can also be achieved practically. As many previous works about the realization of tunable nano-devices based on the electro-optics effect of LCs [41,42], our proposed structures are also able to be fabricated with the help of modern nano- machining technologies. In addition, the special requirement for the excitation of valley states can be easily solved by using point-like chiral sources composed of four-antenna with proper phase lags and narrow Gaussian beams.…”
Section: Discussionmentioning
confidence: 91%
“…LC molecules will in general align with an impressed electric field, which allows for the material phase to be modified using an appropriately oriented external voltage or by illumination at a specific frequency and polarization. In addition to affecting the anisotropy of the material, phase changes in an LC can also alter the plasmonic behavior of nearby metals . This makes LCs an attractive tuning medium to apply to optical metasurfaces.…”
Section: Liquid Crystals (Lcs)mentioning
confidence: 99%
“…In an alternate approach, a zigzag metasurface was suspended in LC and charged to untwist the LC and generate a 110 nm transmission red‐shift . Explicit plasmonic interaction between the LC and metasurface has also been used to create a voltage tunable plasmon induced transparency effect, voltage tunable dynamic plasmonic color filter using an aluminum grating, and a polarization‐independent tunable reflection color modulating nanostructure which can be seen in Figure a . Lee et al showed that a color‐tunable mirror can be voltage controlled by broadening the CP bandwidth of a polymer‐stabilized cholesteric LC layer .…”
Section: Liquid Crystals (Lcs)mentioning
confidence: 99%
“…In this way, one can extend the properties of one GMRF and combine different properties from other GMRFs into one. For example, LCs can be used as a tunable material for a GMRF to rapidly change the resonance peak via modulation of the LC refractive index with an applied voltage 12 . However, there are still many problems.…”
Section: Introductionmentioning
confidence: 99%